Cardiovascular Outcome of the SGLT2 Inhibitor in Acute Myocardial Infarction: A Meta-Analysis - Siqi Hu; Ting Tang; Qingwen Yu; Xuhan Tong; Yao You; Shenghui Zhang; Chen Chen; Jiake Tang; Chunyi Wang; Hu Wang; Xinyan Fu; Juan Chen; et al. (Reviews in Cardiovascular Medicine, 2025)
Background: Unexpected cardiovascular events are likely to occur within a short period following an acute myocardial infarction (AMI). The sodium-glucose co-transporter 2 inhibitor (SGLT2-I) is a recently recommended drug for the treatment of AMI. However, its role in the risk of the outcomes following an AMI, including all-cause death and heart failure readmission, remains controversial. Therefore, in this study, we explored the effect of SGLT2-Is on cardiovascular outcomes after an AMI. Methods: PubMed, Web of Science, and Embase were searched without language restrictions to retrieve case-control studies published before April 2024. Citations were independently screened by two authors, and the studies meeting the predefined inclusion criteria were retained. Data on author names, year of publication, location of the study group, gender and age of participants, outcome assessment, adjusted odds ratios (ORs) and 95% confidence intervals (CIs), and the follow-up period were extracted. Results: Eight studies were eligible for inclusion, and these studies showed that the use of SGLT2-Is after an AMI was significantly associated with a lower risk of hospitalization for heart failure (OR: 0.66, 95% CI 0.57–0.76, p < 0.01) and a lower incidence of major cardiovascular adverse events (OR: 0.79, 95% CI 0.70–0.89, p < 0.01), but was unrelated to a lower incidence of all-cause mortality (OR: 0.84, 95% CI 0.69–1.02, p = 0.07). Conclusions: Compared with placebo, SGLT2-I therapy following an AMI can reduce the risk of heart failure hospitalization and the incidence of major cardiovascular adverse events, but has no effect on all-cause mortality. The PROSPERO registration: CRD42024542335, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024542335.